Epicurus : an introduction to his practical ethics and politics - Erler, Michael (Schwabe Verlag, 2020)
This new introduction into Epicurus? practical ethics and politics provides an overview of Epicurus? attitudes towards political, religious and cultural traditions. Emphasising his claim that philosophy is an art of living that helps people to achieve individual happiness, the book pays special attention to Epicurus? understanding of philosophy as caring for the soul of one?s own. It explains how this Epicurean self-care is connected with caring for others since a happy life requires security that can almost only be found in a community. Epicurus? practical ethics includes a special appreciation of friendship and a conception of ?politics? which indeed focuses on caring for the souls of others. It thus stands firmly in the Socratic tradition. This understanding of practical ethics contributed significantly to the fact that, despite many hostilities, at least practical ethical aspects of Epicurus? teachings were still discussed in the Greco-Roman Empire and sometimes even appreciated by early Christian philosophers.